Geophysical Signature of the Southern Gurubang Base Metal Occurrence in South Eastern NSW. Issue 1 (1st December 2018) - Jones, Harrison; Lackie, Mark; Smith, Mike; Nimalsiri, Thusitha
Abstract : Ground-based, time-domain electromagnetic, magnetic and gravity datasets were obtained for the southern-section of the Gurubang VHMS deposit located approximately 15 km east of Cooma, NSW. The Gurubang deposit is hosted in a mid-late Silurian sequence of rock composed of shallow marine sediments and felsic volcanic rocks. The aim of this research was to ascertain the usefulness of high-resolution geophysical techniques in targeting and evaluating a small-scale polymetallic massive sulphide deposit, and to investigate how the detailed geophysics relates to the overall geological framework of the prospect area. The acquired data was analysed using a forward modelling approach. Due to the deposits high concentration of conductive minerals, a coincident loop time-domain electromagnetic 2D survey effectively delineated the sulphide mineralisation, and was useful in interpreting and adapting deposit parameters such as the azimuth, dip and strike length. Based on the physical nature of the target deposit, it was determined that high-resolution magnetic and gravity surveys would not be effective methods in directly delineating these smaller-scaled (10's of m's) mineral deposits. However, magnetics and gravity did prove effective in depicting the surrounding geology, including potential volcanic intrusions and basement lithologies and structures.